Packaging technologies for the control of stored-product insects - Scheff, Deanna Sue (Kansas State University, 2016)
Larvae of the Indian meal moth, Plodia interpunctella (Hübner), have the ability to invade or penetrate packaging materials and infest the food within. Energy bars with three polypropylene packaging types were challenged with eggs (for first instars), third, and fifth instars of P. interpunctella to determine package resistance to larvae at 28°C and 65% r.h. to determine which provided the greatest protection against P. interpunctella larval penetration. Third and fifth instars showed a higher propensity to infest all packaging variations. First instars showed a reduction in package pentration abiltiy compared to third and fifth instars. Methoprene is an insect growth regulator labeled in the USA for use as an aerosol spray, a residual surface treatment, and as a grain protectant, and recently has been impregnated into a polymer-based packing film to prevent insect infestations of packaged products. The objectives of these studies were 1) determine the effect of short term exposure time and temperature on four week old larvae, continual exposure on egg-to-adult emergence of beetles, and sub-lethal effect on adults of the red flour beetle, Tribolium castaneum (Herbst) and warehouse beetle, Trogoderma variabile Ballion, on the inside and outside surfaces of methoprene-treated woven packaging material at 27 and 32°C at 60% r.h.; 2) evaluate fecundity, egg hatch, and egg-to-adult emergence of T. castaneum and T. variabile, when exposed to two methoprene-impregnated polymer packaging on the inside and outside surfaces at 27 and 32°C at 60% r.h.; and 3) determine the effect of methoprene-treated foil packaging on larval emergence, penetration, and invasion ability of T. variabile and P. interpunctella at 27°C and 60% r.h. Short term exposure results indicated that adult emergence from larvae of T. castaneum and T. variabile decreased with increasing exposure time. The number of eggs laid per female of T. castaneum and T. variabile did not vary from their controls. Continual exposure demonstrated 100% supression of T. castaneum adult emergence, irrespective of exposure to outside or inside surfaces. T. variabile exposed to inside surfaces were unaffected and normal adult emergence was reduced in those exposed to outside surfaces.. The number of T. variabile eggs laid per female was not significantly different among polymer packaging types. The methoprene-treated polyethylene terephthalate to polyethylene packaging, PET-PE reduced the number of T. castaneum eggs laid per female. Both polymer packaging reduced the percent hatch of both species. No T. castaneum adults emerged on the inside surface of PET-PE and both sides of the polyethlyene to polyethylene (PE-PE). Egg-to-adult emergence of T. variabile was arrested at the pupal stage on the outside surface of PE-PE packaging. The PET-PE packaging greatly reduced the number of normal adults by 87 to 97% when exposed to inside surfaces at both temperatures. The foil packaging had no significant effect on hatch of either species. T. variabile were unable to penetrate/invade any foil packages. P. interpunctella invaded all packaging containing pinholes. Therefore, continual exposure of T. castaneum and T. variabile to methoprene impregnated packaging could be a vaiable tool to protect food packages.
Keywords: methoprene; packaging resistance; Plodia interpunctella; Tribolium castaneum; Trogoderma variabileStored-product insects